Drawing on fire: children’s knowledge and needs after a wildfire disaster in Portugal - Ribeiro, Sofia (2020)
There is growing international concern about the impact of natural hazards and disasters on children and young people. However, very little research has explored children’s views of their wildfire experiences. Using creative methods with two groups of primary school children from an inland area, this qualitative study examines Portuguese children’s experiences of a wildfire disaster that affected their community in 2017. An inductive qualitative approach was used to explore the children’s interpretations of this particular event. The children reported high levels of exposure to the wildfire, either directly (in confronting the actual fire) or indirectly (by observing its impact on nature and their community). The implications of these findings are considered in relation to children’s roles in wildfire risk reduction and response.